KONTROVERSI PENULISAN RASM AL-QUR’AN DALAM MUSHAF DIGITAL: STUDI KASUS PERBEDAAN RASM ‘UṮMĀNĪ DAN IMLĀ’Ī DI ERA KONTEMPORER - Ikhlash Hidayatullah; Mhd. Khairi Siddqi; Muhammad Radit Fazilah; Ali Akbar; Edi Hermanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The advancement of digital technology has significantly transformed the way Muslims access the Qur’an, particularly through the emergence of digital muṣḥafs across various applications and online platforms. However, this accessibility has also introduced new challenges, especially concerning differences in the orthographic writing of the Qur’an between the classical ‘Uthmānī script (rasm ‘Uṯmānī) and the simplified imlā’ī script. These differences have sparked controversy regarding the authority of Qur’anic orthography, the authenticity of the text, and the potential for misunderstanding among contemporary audiences. The findings indicate that while the differences between ‘Uthmānī and imlā’ī scripts do not alter the essential wording of the Qur’an, they may lead to confusion in learning and interpretation if not supported by adequate literacy. Furthermore, inconsistencies across digital platforms highlight the absence of a unified global standard for digital muṣḥaf orthography. From the perspective of ulūm al-Qur’an, the ‘Uthmānī script remains the authoritative standard, and its consistent implementation in digital media is essential. Therefore, this study emphasizes the need for reconstruction efforts, including the standardization of digital muṣḥafs, strengthening the role of authoritative institutions, and enhancing public literacy in ulūm al-Qur’an. In doing so, digital advancements can be utilized effectively without compromising the authenticity and authority of the Qur’anic text as a preserved revelation.